Properties of Jute Fibre Reinforced Polymer Composites – A Review (European Journal of Engineering Science and Technology, 2023)
Jute fibres is of great interest to be used as reinforcement in thermoset or thermoplastic composites, in order to provide positive environmental benefits in-terms of degradability, abundance, low density, nominal cost and recyclable. During fabricating the composites, researchers facing complications such as high water absorbing (WA) character, poor incompatibility of fibre with resins, quality variations in fibres, low thermal stability, etc. Therefore, chemical treatments are considered and it will be the most effective way to enhance the interfacial bonding with matrix, improve mechanical strength and less WA as well. Many research works were carried out on the influence of chemical treatment on the properties of jute fibre and their composites. The investigated treatment methods and the impact of chemical treatment on the properties of jute fibre reinforced polymer composites are comprehensively presented in this review.